2017
DOI: 10.1002/cplu.201700198
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis‐Initiated Domino Process on the Rim of Open‐Cage C60 Derivatives Including Decarbonylation and Double Dehydration

Abstract: Hydrolysis of an open‐cage C60 derivative in a mixture of HCl/AcOH/H2O resulted in removal of two hydroxyl groups, one carbonyl group and one aniline group in one step. A domino mechanism is proposed for the process. The newly formed open‐cage C60 derivative has three carbonyl groups on the rim of the orifice, one of which could be converted into an oxime group by treatment with hydroxylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Recently we reported the synthesis of the open‐cage fullerene derivative 3 which has an oxime group on the rim of the orifice [22] and used it as a ligand to form palladium complexes [23] . Further study shows that the precursor compound 1 could also form analogous oxime derivative 4 under the same conditions (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we reported the synthesis of the open‐cage fullerene derivative 3 which has an oxime group on the rim of the orifice [22] and used it as a ligand to form palladium complexes [23] . Further study shows that the precursor compound 1 could also form analogous oxime derivative 4 under the same conditions (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The new compounds 4 – 10 were characterized by spectroscopic data. Compound 4 exhibits no symmetry due to the presence of the oxime group, which is analogous to compound 3 [22] . It showed three carbonyl chemical shifts at 185.37, 184.20, and 177.98 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The decarboxylation process to form 3 from 2 may be initiated from a formal 1,5‐H shift in which the NH proton shifts to the lactone oxygen resulting an ɑ‐imino carboxylic acid group, followed by the decarboxylation similar to the classical organic compound. In our previous study [29] we reported several acid‐induced hydrolysis and rearrangement routes for compounds with analogous structures to compound 1 but without the epoxy moiety. The present results are different from all the previous pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The open-cage fullerenes 1 – 3 were prepared through a fullerene-mixed peroxide method in a multiple step sequence. Addition of Pd­(PPh 3 ) 4 to compound 1 in a 1:1 ratio resulted in the monoadduct 4 in a few minutes.…”
Section: Resultsmentioning
confidence: 99%